Social Work and Sustainable Development Goals: Role of Social Workers in Improving Well-Being for Residents of Nursing Homes in Malaysia - Adam Andani, Mohammed; Athirah, Azhar (2021)
The traditional role of social work includes but not limited to addressing issues of inequality, violence, substance abuse, isolation, discrimination and social well-being. The values and principles of the SDG are geared towards the creation of a cohesive and equitable society in a more transformative manner. In addressing social well-being, nursing homes are set up for people who do not need to be hospitalize but cannot be cared for at home. These people are supposed to be managed by professional and skilled nurses, doctors and social workers. As such, this study focuses on the services and advocacy of social workers to help nursing homes achieve an improved sense of well-being. To get relevant data, Google Scholar was used as a tool to access the major databases provided by Tailor and Frances, Emerald, Elsevier, Springer, Sage and others. The study found that the service and advocacy of social workers produce a significant impact on the individuals at nursing homes. The study contributes to knowledge by critically exploring and synthesizing the role of social work in response to welfare services to reduce inequality, enhance good health and wellbeing of the people in nursing homes as indicated in SDGs 3 and 10.